Technostress and Personnel Flourishing: A Longitudinal Study on the Impact of AI-Driven Monitoring on Psychological Well-being - Mukhlis Mukhlis; Syafiq Amir; Haziq Idris (Yayasan Adra Karima Hubbi, 2026)
The rapid integration of artificial intelligence (AI)–driven monitoring systems in contemporary workplaces has transformed performance management practices and intensified digital supervision. While such systems promise efficiency and data-driven decision-making, concerns have emerged regarding their psychological consequences. Technostress theory suggests that continuous technological exposure may generate strain, yet limited longitudinal evidence exists on how AI-based monitoring influences personnel flourishing over time. This study aims to examine the dynamic relationship between AI-driven monitoring intensity, technostress dimensions, and psychological well-being using a longitudinal framework. A three-wave panel design was implemented with full-time employees working in organizations utilizing AI-based performance analytics. Data were collected at four-month intervals and analyzed using cross-lagged structural equation modeling to assess causal pathways and moderating effects. Measures included monitoring intensity, technostress dimensions, flourishing indicators, perceived organizational support, and digital literacy. Results indicate that AI-driven monitoring significantly predicts increased technostress, particularly techno-invasion and techno-overload, which subsequently reduce personnel flourishing across time. Technostress mediates the relationship between monitoring and well-being, while organizational support buffers negative effects. Partial adaptation was observed but did not fully restore flourishing levels. The findings underscore the importance of human-centered AI governance to sustain psychological well-being in digitally monitored workplaces.